THE INTERPLAY BETWEEN BLENDED LEARNING AND STUDENTS' LEARNING MOTIVATION AND ACHIEVEMENT - Bactiar, Bactiar; Kaspirawati, Yuni; Juhana, Juhana (English Education Department, 2023)
This study aims to investigate the correlations between students’ perceptions on blended learning implemented in English teaching during the adaptation to the new normal, students’ motivations in learning English and students’ achievements in English subject. The participants of this study are 237 11th grade students of SMAN 1 Sukaresmi who had experienced blended learning method more than one year. This study uses the questionnaire adapted from model of Birbal et al. and Gardner’s Attitude/Motivation Test Battery, and IBM SPSS Statistic 27 to calculate the data. There is significant and positive correlation between students’ perceptions on blended learning implemented in English teaching at SMAN 1 Sukaresmi during the adaptation to the new normal and students’ achievements in English subject, between students’ motivations in learning English and students’ achievements in English subject, and between students’ perceptions on blended learning implemented in English teaching at SMAN 1 Sukaresmi during the adaptation to the new normal and students’ motivations in learning English. Partially, no influence is exerted by students' perceptions on blended learning implemented in English teaching at SMAN 1 Sukaresmi during the adaptation to the new normal on students' achievements in English subject. Meanwhile, the considerable influences are exerted by students' motivations in learning English on students' achievements in English subject. However, when they are together, they will have an effect of 21.1% on students' achievements.